2021
DOI: 10.1055/a-1582-9794
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Kinetics as Key Determinant in Toxicity of Pyrrolizidine Alkaloids and Their N-Oxides

Abstract: Pyrrolizidine alkaloids (PAs) are a large group of plant constituents of which especially the 1,2- unsaturated PAs raise a concern because of their liver toxicity and potential genotoxic carcinogenicity. This toxicity of PAs depends on their kinetics. Differences in absorption, distribution, metabolism, and excretion (ADME) characteristics of PAs may substantially alter the relative toxicity of PAs. As a result, kinetics will also affect relative potency (REP) values. The present review summarizes the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
(133 reference statements)
0
4
0
Order By: Relevance
“…Thus, the toxicity and, thereby, also the REP PANO to PA value of PANOs depend on the rate and extent of PANO reduction to the parent PA and other kinetic factors such as absorption that would influence what the liver is exposed to. Although the PANO reduction in the liver may be included in the in vitro cell model used, these models generally do not consider the PANO reduction by the intestinal microbiota, nor do they accommodate gastrointestinal uptake 34 , 35 . Another factor that may influence the REP PANO to PA values is that the in vivo studies from which these REP PANO to PA values can be derived are generally performed at relatively high equimolar doses of the PANO and PA in order to enable detection of selected biomarkers, while estimated daily dietary intake for the human population occurs at dose levels that may be orders of magnitude lower 1 .…”
Section: Relative Potency Factors Of Pa N -Oxides At ...mentioning
confidence: 99%
“…Thus, the toxicity and, thereby, also the REP PANO to PA value of PANOs depend on the rate and extent of PANO reduction to the parent PA and other kinetic factors such as absorption that would influence what the liver is exposed to. Although the PANO reduction in the liver may be included in the in vitro cell model used, these models generally do not consider the PANO reduction by the intestinal microbiota, nor do they accommodate gastrointestinal uptake 34 , 35 . Another factor that may influence the REP PANO to PA values is that the in vivo studies from which these REP PANO to PA values can be derived are generally performed at relatively high equimolar doses of the PANO and PA in order to enable detection of selected biomarkers, while estimated daily dietary intake for the human population occurs at dose levels that may be orders of magnitude lower 1 .…”
Section: Relative Potency Factors Of Pa N -Oxides At ...mentioning
confidence: 99%
“…There is a rising concern for food safety issues related to the consumption of THIs, which may pose challenges to public health due to toxic secondary metabolites (e.g. phytates and pyrrolizidine alkaloids) [ [36] , [37] , [38] , [39] , [40] ], contaminants [ [41] , [42] , [43] , [44] ] or contamination with other plant species. For instance, a recent quality assessment of marketed herbal infusion showed that chamomile crude flowers were most likely to be adulterated by other plant materials compared to chamomile bags [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 ] Another reason for the selection was that for SENO kinetic data from an in vivo rat study [ 11 ] are available for PBK model evaluation. Given that different PAs show different kinetic profiles, [ 33 ] different PA‐N‐oxides might also demonstrate different kinetic profiles due to potential structure‐dependent differences in reduction of the N‐oxides to the parent PAs [ 20 ] and in metabolic clearance of the formed parent PAs. [ 34 ] Besides structure‐dependent differences, there might also be species‐dependent differences in the kinetics of PAs and their N‐oxides potentially resulting in different REP values in rat and human.…”
Section: Introductionmentioning
confidence: 99%